Effectiveness of Kami Prihatin charity programme during the covid-19 outbreak / Ainorkhilah Mahmood … [et al.] - Mahmood, Ainorkhilah; Elias, Muhammad Ismail; Bakhari, Nor Aziyah; Othman, Nor Azlan; Abdul Hamid, Haslinda (2021)
The standard of living has a significant impact on one's quality of life. However, as the standard of living rises, so will consumer spending on products due to rising commodity costs. As a result, low-income households (B40) and needy people face difficulties. The government and non-governmental organizations have established many charity programmes to address this issue. Thus, the purpose of this study is to assess the effectiveness of a charity programme, Kami Prihatin 4.0, in assisting people in need during the COVID-19 outbreak. In total, 143 respondents participated in the study. A set of questionnaire was prepared to collect all of the essential data. The questionnaire was adaptedfrom previous study which originally used to used to gauge the perception of charitable giving in general. The questionnaire is divided into five sections. The sections comprise of demographic profile of the respondents, general perception, progamme’s donation, progamme’s flow and regarding the understanding of speech about COVID-19. Before the programme began, each participant was handed one per individual, which was subsequently collected when the session ended. The findings revealed that the majority of the participants have positive feelings about the programme because it benefits not only them but also the organizer. Furthermore, the participants agreed that this programme should be held even during the COVID-19 pandemic. The majority of them would be more likely to attend the programme even during a crisis. This study demonstrates that charity programmes have a positive influence on low-income families. As a result, efforts to aid poor people during a crisis are critical to alleviating their suffering.